2006
DOI: 10.1063/1.2168454
|View full text |Cite
|
Sign up to set email alerts
|

Spectral phase effects on nonlinear resonant photochemistry of 1,3-cyclohexadiene in solution

Abstract: We have investigated the ring opening of 1,3-cyclohexadiene to form 1,3,5-cis-hexatriene (Z-HT) using optical pulse shaping to enhance multiphoton excitation. A closed-loop learning algorithm was used to search for an optimal spectral phase function, with the effectiveness or fitness of each optical pulse assessed using the UV absorption spectrum. The learning algorithm was able to identify pulses that increased the formation of Z-HT by as much as a factor of 2 and to identify pulse shapes that decreased solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 58 publications
6
64
0
Order By: Relevance
“…Tunable noncollinear optical parametric amplifiers and programmable acousto-optic pulse shapers were used in this work, together with standard white light ultrafast probe techniques (46,47). The details are discussed in SI Text.…”
Section: Methodsmentioning
confidence: 99%
“…Tunable noncollinear optical parametric amplifiers and programmable acousto-optic pulse shapers were used in this work, together with standard white light ultrafast probe techniques (46,47). The details are discussed in SI Text.…”
Section: Methodsmentioning
confidence: 99%
“…46,47 Finally, and perhaps most importantly, CHD has been used extensively to demonstrate new techniques and concepts. This includes coherent control, both experiment 43,48,49 and theory, 7,50,51 and a range of new ultrafast imaging techniques 52 such as electron diffraction, [53][54][55][56] X-ray scattering, 44,45 Coulomb explosion, 57 and near-edge X-ray absorption fine structure (NEXAFS). 58 The variety of complementary observations generated by these techniques holds great promise for tying down a complete understanding of this important and complex reaction, for instance by combining X-ray scattering and photoelectron data such as in ref.…”
Section: Introductionmentioning
confidence: 99%
“…This process has been extensively studied, in part because of its role in vitamin D biosynthesis. Time-resolved pump-probe techniques have been employed to understand this process [20][21][22][23][24][25]. These studies have found that the conical intersection-mediated ring-opening step in isomerization is completed in less than 200 fs [22], after which the molecule undergoes conformational changes on a range of timescales (see inset in Fig.…”
mentioning
confidence: 99%